PENGARUH PENERAPAN MODEL PEMBELAJARAN PJBL BERBANTUAN GALLERY WALK TERHADAP KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VIII DI SMPN 13 MALANG - Ayu Nazar; Djoko Soelistijo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Based on observations conducted in class VIII E of SMP Negeri 13 Malang, social studies (IPS) learning was dominated by lectures and conventional assignment methods. During the learning process, the teacher still dominated the delivery of material, while students tended to act merely as listeners and note-takers. As a result, most students appeared less enthusiastic, easily bored, reluctant to ask questions, and tended to remain silent when given the opportunity to discuss. This phenomenon indicates that students' learning activeness in social studies is still relatively low and requires special attention. This study aims to determine the effect of implementing the Project-Based Learning (PjBL) model combined with Gallery Walk on students' learning activeness in the Social Studies (IPS) subject. This study used a quantitative approach with a Pre-Experimental design through a One Group Pre-Test–Post-Test design. The research subjects consisted of 32 students from class VIII E at SMPN 13 Malang, selected using Purposive Sampling technique from the entire population of eighth-grade students. The results showed that the implementation of the Project-Based Learning (PjBL) model assisted by Gallery Walk had a positive and significant effect on students' learning activeness. The implementation of this model was able to encourage students to participate more actively, engage in learning activities, and increase interaction during the social studies learning process.